REAL-TIME PCR TO IDENTIFY PORCINE DNA IN PROSTHODONTIC MATERIALS - Ismail Hutasoit; Agy Pranata; Masna Wiyah; Fitri Ramadhani; Hubban Nasution (Cumhuriyet University, 2021)
Objectives: This study aimed to identify porcine DNA in prosthodontic materials using Real-Time PCR. Materials and methods: Eighteen prosthodontic materials: three irreversible hydrocolloids, three elastomers, three denture adhesives, three soft denture linings, three temporary crowns, and three denture bases materials were used as the samples. It was conducted in two stages. First, extraction of dental material's DNA and the second was Real-Time PCR analysis based on amplification curve and Ct score in yellow and green channel. Results: The sample analysis based on green channel demonstrated that all materials did not contain porcine DNA, however, 11 of 18 samples (DA-01, DA-02, DA-03, SDL-02, DB-01, DB-02, TC-03, IH-02, EM-01, EM-02, and EM-03) contained vertebrate DNA. Conclusions: All prosthodontic materials tested were not containing porcine. The halal statues of the materials were still unclear.